Literacy Study of Tcfl Teacher Competencies - Sofi Zhang (Humaniora, 2012)
TCFL teachers’ competencies are a new and popular field of research in the Chinese language. These competencies will relate to the knowledge and skills that TCFL teachers should have, such as the knowledge in linguistics and Chinese linguistics, theory of the second language, learning strategies and teaching methodologies. Beside that, teacher should have a good awareness, psychological and emotional control. This article summarizes the results of literacy study of TCFL teachers’ competencies. At first, these seem difficult to achieve, but by consistently accumulating teachers' knowledge and skills, its can help to give new TCFL teachers a clearer understanding of their role in education and help them make preparations. Accumulating knowledge and skills, controlling the role of psychology and emotions are very important that TCFL teachers must have as their lifestyle.